2010
DOI: 10.2478/v10042-010-0012-4
|View full text |Cite
|
Sign up to set email alerts
|

The estimation of oxidative stress markers and apoptosis in right atrium auricles cardiomyocytes of patients undergoing surgical heart revascularisation with the use of warm blood cardioplegia.

Abstract: Abstract:Oxidative stress markers and apoptosis were estimated during elective surgical heart revascularization. Eight patients with good ejection fraction underwent coronary artery bypass grafting (CABG) with the use of warm blood cardioplegia. Two right atrium auricle biopsy specimens were collected before and after the operation. Specimens underwent immunocytochemical analysis of mitochondrial manganese superoxide dismutase (MnSOD) expression and apoptosis estimation by the TUNEL method. Ultrastructure anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
(40 reference statements)
0
4
0
Order By: Relevance
“…Ferrari et al reported a significant and sustained increase in OS in 10 patients undergoing ONCABG with a mean XC duration of 55.2 minutes, while a mild and temporary increase in OS in 10 patients undergoing ONCABG with a mean XC duration of 25.2 minutes [ 17 ]. Nowicki et al also reported the absence of a significant oxidative damage in the myocardial biopsy specimens of 8 patients undergoing ONCABG with a mean XC duration of 29.5 minutes [ 18 ]. To our knowledge, this paper is the first in the literature which reported neither systemic oxidant increase nor systemic oxidative imbalance occurred in patients with a mean XC duration of 29 minutes (group 1) by evaluating TOS and OSI.…”
Section: Discussionmentioning
confidence: 99%
“…Ferrari et al reported a significant and sustained increase in OS in 10 patients undergoing ONCABG with a mean XC duration of 55.2 minutes, while a mild and temporary increase in OS in 10 patients undergoing ONCABG with a mean XC duration of 25.2 minutes [ 17 ]. Nowicki et al also reported the absence of a significant oxidative damage in the myocardial biopsy specimens of 8 patients undergoing ONCABG with a mean XC duration of 29.5 minutes [ 18 ]. To our knowledge, this paper is the first in the literature which reported neither systemic oxidant increase nor systemic oxidative imbalance occurred in patients with a mean XC duration of 29 minutes (group 1) by evaluating TOS and OSI.…”
Section: Discussionmentioning
confidence: 99%
“…Increased ROS production and, more specifically, increased superoxide anion production derived from the atrial nicotinamide adenine dinucleotide phosphate oxidase are independently associated with a higher risk of POAF supporting an association between ROS in human atrium and POAF [ 44 , 45 ]. Furthermore, atrial tissue from patients in whom POAF developed displayed an upregulation of mitochondrial MnSOD activity and an increased sensitivity of mPTP opening [ 45 , 46 ].…”
Section: Oxidative Stress Inflammation and Cardiopulmonary Bypasmentioning
confidence: 99%
“…In our research significant increase in MnSOD expression was observed, but not specific correlation between the intensity of reaction, the percentage of stained cells, and incubation time were found, neither no difference between Custodiol and Plegisol were noted. Previously, we examined the expression of MnSOD in the right atrium appendage of the cardioplegicaly arrested heart during coronary revascularization [ 26 ]. As we observed, the MnSOD expression increased in sections of the right atrium appendage by the rise of stain intensity and the percentage of cells with positive stain.…”
Section: Discussionmentioning
confidence: 99%